2008
DOI: 10.1364/josaa.25.001215
|View full text |Cite
|
Sign up to set email alerts
|

Role of color memory in successive color constancy

Abstract: We investigate color constancy for real 2D paper samples using a successive matching paradigm in which the observer memorizes a reference surface color under neutral illumination and after a temporal interval selects a matching test surface under the same or different illumination. We find significant effects of the illumination, reference surface, and their interaction on the matching error. We characterize the matching error in the absence of illumination change as the "pure color memory shift" and introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…Recently, a study by Ling and Hurlbert (2008) investigated how colour memory affects successive colour constancy. They found that memory is a limiting factor on constancy and that, once memory was taken into account, colour constancy was nearly perfect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study by Ling and Hurlbert (2008) investigated how colour memory affects successive colour constancy. They found that memory is a limiting factor on constancy and that, once memory was taken into account, colour constancy was nearly perfect.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, photographs of natural scenes seen in color are recognized quicker and remembered better than when grayscale is used [19,20] and even in the case of simple lights, chromatic components are better remembered than brightness ones [21]. Our ability to remember colors has been put to practical use in applications such as color quality metrics for solid-state light sources [22] and to enhance digital images [23] and plays a significant role in color constancy [24][25][26][27].Given this important role of color in visual memory, large biases would be somewhat surprising. However, our results do confirm previous studies in finding an increase in saturation in the memory construct compared to direct viewing.…”
mentioning
confidence: 99%
“…Finally, twoway ANOVA was used to observe the IR performance of the high-score group. ''Hue factor'' passed the test for significance (F (1.26) ¼ 16.54, P ¼ 0.000 \ 0.005); the ''Brightness factor'' also passed the test for significance (F (1,26) ¼ 5.107, P ¼ 0.032 \ 0.05). However, the interaction between the two did not pass the test for significance.…”
Section: Figmentioning
confidence: 95%
“…Whether brightness guidance was shown or hidden did not pass the test for significance; hence, this meant that the brightness factor had no significant influence on the high-score group's IR. However, after conducting the T-test for the hue factor, whether the hue guidance was shown or hidden in a ''Brightness Shown'' context made a difference to the IR of the high-score group and passed the test for significance (T (26) However, the trend of the loci in Fig. 9(a) showed a similar performance from the high-score group and the mid- score group.…”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation